Patogen Penyakit Busuk Buah Kakao: Karakter dan Patogenisitas Phytophthora palmivora Isolat Asal Pakuwon, Sukabumi - Wartono Wartono; Efi Taufiq (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Phytophthora palmivora (Butl.) is a major obstacle in cocoa cultivation worldwide. The study aimed to determine the morphological character and pathogenicity of P. palmivora Pakuwon isolate. The study was carried out from November 2020 to January 2021, which consisted of 3 activities e.g. (1) pathogen isolation, tests on growth rate and colony formation, and stimulation of sporangia, zoospore, and clamydospore formation, which was performed in CMA, PDA, and mung bean media. The parameters observed were colony shape, growth rate, shape and size of sporangia, papillae, and sporangiophores, also chlamydospore and hyphal diameters; (2) To determine the possibility of different mating types, two isolates were grown on CMA medium in one petri dish; (3) The pathogenicity test, using a detached fruit assay by inoculating the cocoa pods with mycelium plug and zoospores. The patogenicity test was conducted in a completely randomized design with 4 replications, and the parameter observed was the area of the spot. The isolation obtained 3 isolates, the mycelium of all three isolates showed white in color, cottony, and no pattern in shape. The diameters of hyphae and chlamydospores were 5.6 - 6.3 mm and 39.0 - 43.2 mm, respectively. The sporangia were ovoid, ellipsoid, subsperic, obpyriform, and irregular. Sporangia measured 5.6 - 60.1 mm in length and 30.4 - 32.9 mm in width. Papillae were obviously visible with an average length of 6.8 mm. Test on mating types showed no oospores formed. PPkw1 isolates showed higher growth rates and more pathogenic than PPkw2 and PPkw3. The difference of pathogenicity of each P. palmivora isolates originated from Pakuwon can be used for selection of cocoa resistance in the future.